Mobile technology and flipping book: new marketing trends in IIUM Library - Abd Samad, Zaharah; Razali, Leenawati (2014)
This paper highlights the implementation of new marketing initiative at the Library of International Islamic University Malaysia. The Library has developed new service, a special collection on Muslim Scholar’s profile. There are 168 Muslim Scholars profile in printed poster format exhibited at the Islamic Intellectual Heritage Gallery at level 2, library building. This collection is considered as an essential reference for research in Islamic history and civilization. However, access to this information is limited as it is available in printed format only. Therefore, new marketing initiatives are established to promote this new service to increase awareness among existing users, researchers and external members. These initiatives providing access to the information on the Muslim Scholar’s profile through mobile devices and flipping book. The development of the flipping book of Muslim Scholar profile collection will be elaborated. Besides that, the role of Quick Reading Codes (QR-code) in the marketing of Muslim Scholars Profile Collection also will be presented. The usage and feedback from users on these new initiatives will be discussed. Finally, the future of mobile technology and flipping book in marketing of the library services will be briefly discussed.